The Innovation of Gender Mainstreaming Implementation: A Study on Gender Festival at the Ministry of Environment and Forestry - Muhammad Nurfathurrohman; Ismi Dwi Astuti Nurhaeni (Universitas Muhammadiyah Yogyakarta, 2024)
Government agencies need to carry out public policy innovations to deal with changes that occur quickly and dynamically. The Ministry of Environment and Forestry (MoEF) developed an innovation called the Gender Festival as an effort to transform a